Proceedings of the 2006 International Workshop on Global Software Development for the Practitioner 2006
DOI: 10.1145/1138506.1138513
|View full text |Cite
|
Sign up to set email alerts
|

The processes of joining in global distributed software projects

Abstract: Libre (free / open source) software is a good example of global software development. Thousands of projects, in a wide range of domains which involve hundreds of thousands of developers and contributors from all around the world. Some large (both in size and developer community) libre software projects have shown evidence of producing code with complete functionality and fast evolution (with linear or superlinear growth), while maintaining low defect density. Many companies are exploring how to benefit from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 14 publications
0
56
0
Order By: Relevance
“…In fact, four studies in our sample found that open-source projects had lower cognitive complexity and were more modular than proprietary projects (Herraiz et al, 2006;MacCormack et al, , 2008Baldwin et al, 2014). However, three other studies found no evidence of strict partitioning within codebases nor any correspondence between identifiable organizational groups and specific modules (Bird et al, 2008;Bowman and Holt, 1998;Gutwin et al, 2004).…”
Section: The New Economics Of Digital Tools and Technologiesmentioning
confidence: 72%
“…In fact, four studies in our sample found that open-source projects had lower cognitive complexity and were more modular than proprietary projects (Herraiz et al, 2006;MacCormack et al, , 2008Baldwin et al, 2014). However, three other studies found no evidence of strict partitioning within codebases nor any correspondence between identifiable organizational groups and specific modules (Bird et al, 2008;Bowman and Holt, 1998;Gutwin et al, 2004).…”
Section: The New Economics Of Digital Tools and Technologiesmentioning
confidence: 72%
“…Herraiz et al found that apart from gradual progression, there is another common developer joining pattern, viz., the quick initiation of employees of enterprises invested in that OSS project as new developers [15]. Shibuya and Tamai performed case studies and confirmed these findings on other OSS projects (GNOME, OpenOffice.org, MySQL) [16].…”
Section: Related Workmentioning
confidence: 75%
“…In a still more recent case study focusing on GNOME, 12 Herraiz et al (2006) also ask whether the conventional dynamic interpretation of the onion model is a good representation of the joining process, and seek answers by estimating the distribution of transit times between developers' first instances of performing characteristic tasks in the onion's successive layers. Although it is typical for individuals in the GNOME community to have contacted the project by email before beginning to commit code 13 , conventional suppositions regarding the next step in the sequence are violated by most of the GNOME developers' behaviors: for example, they often commit to the project's CVS before sending their first bug report.…”
Section: Role Differentiation Among Developers: the Background Of Relmentioning
confidence: 99%